URGENSI RAFA’ SEBAGAI SALAH SATU INSTRUMENT SYARAT PENCATATAN PERKAWINAN PERSPEKTIF MASLAHAH AL-SYATIBI: Studi Kasus di Kantor Urusan Agama Jombang - Abd. Basit Misbachul Fitri; Imilda Zakkiyatie (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
In Indonesia, a marriage is considered legally valid by the state if it is recorded by the Marriage Registrar (PPN). This is by Article 2, paragraph 1 of Law No. 1 of 1974 concerning Marriage, which states that every marriage must be registered according to the applicable laws. Before the marriage is recorded, the bride and groom (catin) and the marriage guardian must undergo the rafa’ process. Rafa’ is a prerequisite that must be followed by the bride and groom and the marriage guardian for the marriage to be legally recognized. This study addresses two main issues: (1) What is the mechanism of rafa’ at the KUA of Jombang Subdistrict, Jombang Regency? (2) How is the rafa’ mechanism at the KUA of Jombang Subdistrict viewed from the perspective of Maslahah? This research uses a juridical-empirical approach with a qualitative research type and a descriptive-analytical method. Data collection was conducted through observation, documentation, and interviews, which were then analyzed using the Maslahah Al-Syatibi approach. This study concludes two things. First, the rafa’ mechanism at the KUA of Jombang Subdistrict, Jombang Regency complies with the provisions of Minister of Religious Affairs Regulation No. 20 of 2019. Second, the stages and procedures of rafa’ at the KUA are consistent with the maslahah theory proposed by Imam al-Syatibi, where the maslahah values embedded in rafa’ align with the values derived from Islamic legal sources.